2008
DOI: 10.1111/j.1600-079x.2008.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of melatonin against caustic esophageal burn injury in rats

Abstract: Caustic ingestion is one of the most life-threatening events in the pediatric age group, which requires the immediate management and subsequent treatment of its most significant complication, i.e. alterations in esophageal structure. We investigated whether melatonin could reduce the esophageal burn damage induced by sodium hydroxide. It was assumed that melatonin could be effective because of its function as a direct free radical scavenger, its antioxidative actions and its ability to diminish tissue hydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 82%
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 82%
“…Our previous works and other studies with more rigorous investigation revealed that oxidative stress has a significant role in the affected site of the injured esophageal wall [13][14][15]20]. A variety of antioxidant agents may help to prevent stricture formation in a caustic esophageal burn model in rats [19,[35][36][37]. These observations strongly suggest that caustic esophageal injury is associated with decreased antioxidant activity resulting in increased tissue damage.…”
Section: Discussionmentioning
confidence: 77%
“…Studies with more rigorous investigation revealed that oxidative stress has a significant role in the affected site of the esophageal wall [14,15]. In addition, studies displayed that a variety of antioxidant agents may help to prevent stricture formation in a caustic esophageal burn model in rats [19,[35][36][37]. The development of dense scar tissue at the injury site is a later consequence of caustic esophageal injury [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although several treatment protocols have been devised and used to accomplish anti-inflammatory and anti-fibrogenic actions, the benefit and standardization of these treatment methods are still controversial [3]. Nowadays, the effects of many therapeutic agents in preventing esophageal stricture formation continue to be investigated in experimental caustic esophageal burn injury models [4,5].…”
Section: Introductionmentioning
confidence: 98%